Functionalized quinolones and isoquinolones via 1,2-difunctionalization of arynes: synthesis of antagonist agent AS2717638 and floxacin key intermediates - Mahale, Sachin D.; Prasad, Anamika; Mhaske, Santosh B. (Chemical Communications, 2024)
Quinolones and isoquinolones are privileged scaffolds in synthetic/medicinal chemistry and drug discovery due to their unique chemical structures and intrinsic properties. Herein, we reveal a transition-metal-free approach for their synthesis from the reaction of dimethyl-2-((phenylamino)methylene)malonate with aryne precursors under mild conditions. The substrate scope is broad, accommodating a wide range of functional groups. The synthetic utility of the developed protocol has been demonstrated in the total synthesis of the potent antagonist agent AS2717638 and key intermediates of floxacin congeners. The gram-scale experiments illustrate its synthetic potential.

Regio- and stereoselective construction of 1,3,5-triaroylcyclohexanes via KO t Bu-mediated cyclotrimerization of aryl vinyl ketones - Mahale, Sachin D.; Yadav, Vinita; Gonnade, Rajesh G.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2024)
Herein, we disclose a simple one-pot method for an efficient regio- and stereoselective synthesis of 1,3,5-triaroylcyclohexanes from aryl vinyl ketones using potassium tert-butoxide. The developed protocol allows the construction of various symmetrically substituted cyclohexanes in good to excellent yields. The major product 2 also can be converted to the product 3 (all equatorial) conveniently by acid catalysis. This protocol features a good substrate scope and functional group compatibility.